Peran Orang Tua Dalam Mendukung Kegiatan Pembelajaran Online (Daring) di Masa Pandemi Covid-19: Studi pada orang tua yang memiliki anak usia 6-12 tahun di Kampung KB Sukapala Kelurahan Gunung Gede Kecamatan Kawalu Kota Tasikmalaya - Hanifah Rahmah Sari; Wiwin Herwina; Ahmad Hamdan (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2022)
Parents in the village of KB Sukapala Gunung Gede Village Kawalu Kota Tasikmalaya with the existence of Online learning activities some parents take pains to support or complete learning needs in the Covid-19 pandemic. The school such as teachers or teachers are not only able to provide materials but can understand and understand social, environmental and economic conditions. The purpose of this study is to find out the role of parents in supporting Online learning activities in the Covid-19 pandemic. This method of research uses qualitative descriptive with data collection techniques through observation, interview and documentation studies. The data analysis technique in this study uses miles and huberman models with several flows, namely data reduction(data reduction), data display (presentation of data) and conclustion drawing (village). Based on the results of research obtained that parents act as educators such as teachers at home and encourage children with motivation and become facilitators to meet learning needs and parents also guide with full direction.